Micro-CT evaluation of apical enlargement of molar root canals using rotary or reciprocating heat-treated NiTi instruments - Pinto, Jáder Camilo [UNESP]; Pivoto-João, Mariana Mena Barreto [UNESP]; Espir, Camila Galetti [UNESP]; Ramos, Maria Luiza Gioster [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (FapUNIFESP (SciELO), 2019)
OBJECTIVE: The aim of this study was to evaluate the root canal preparation and apical enlargement of molar root canals with rotary or reciprocating heat-treated nickel-titanium (NiTi) instruments, by using micro-computed tomography (micro-CT). METHODOLOGY: Mesial root canals (n=48) of mandibular molars, with a curvature between 20° and 40°, were prepared with ProDesign Logic (PDL) 25.01 and 25.06 in rotary motion, or ProDesign R (PDR) 25.06 in reciprocating motion (PDR). Apical enlargement was performed with PDL35.01 and PDL35.05 or PDR35.05. Scanning with 9 µm resolution was performed before and after preparation, and, after apical enlargement, by using micro-CT. The percentage of volume increase, debris and untouched root canal surface, transportation, centralization and preparation time were analyzed. ANOVA and Tukey or Kruskall-Wallis and Dunn statistical tests were conducted (α=.05). RESULTS: PDL promoted a higher apical percentage of volume increase, and lower percentage of debris and untouched root canal surface than PDR 25.06 preparation in entire canal and in all thirds (P<.05). Apical enlargement with PDL 35.05 and PDR 35.05 produced a higher percentage of volume increase in the apical region in relation to the initial preparation (P<.05). PDR 35.05 and PDL 35.05 showed similar results in relation to percentage of debris and untouched root canal surface in entire canal and in all thirds (P>.05). Centralization and transportation showed no difference (P>.05). PDR required less time to perform preparation and apical enlargement (P<.05). CONCLUSIONS: The apical enlargement 35.05 with CM heat-treatment instruments using reciprocating and rotary motion reduced the percentage of debris and untouched root canal surface, without causing deviations or procedural errors. The protocol of greater apical enlargement favors the cleaning of the root canals in both kinematics. Preparation by the reciprocating system was faster than by the rotary system.